Problematika Kelembagaan Otoritas Jasa Keuangan (OJK) dalam Pengawasan Pinjaman Online dan Layanan Keuangan Digital di Indonesia - Anggita Lailatun Ni’mah; Bintang Afifah Nailah; Dyah Hayu Woro; Aldi Rizal Syahputra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of the digital economy in Indonesia has driven various innovations in the financial services sector, including online lending services (PINJOL) and digital financial platforms. This phenomenon presents both opportunities and challenges for the national financial supervisory system. The Financial Services Authority (OJK), as the institution authorized to regulate and supervise financial services, is required to adapt its role to these dynamics. This study aims to examine the institutional challenges faced by the OJK in carrying out its supervisory function over online lending services and digital financial services in Indonesia. The methods used in this research are normative juridical, with a statute approach, legal theory and institutional theory (Conceptual approach), case approach, and a comparison of fintech supervisory models with those of other countries (Comparative approach). The results of this study are expected to provide an understanding of the OJK's institutional challenges and serve as evaluation material for formulating future digital financial supervisory policies.